Bracketed stub loaded single layer rectangular microstrip antenna: A novel approach for modulation of magnetic field locus to achieve improved matching, and low cross polarisation. Issue 11 (13th June 2019) - Pawar, Umesh Ankush; Ghosh, Abhijyoti; Chakraborty, Subhradeep; Lolit Kumar Singh, L.; Chattopadhyay, Sudipta; Sim, Chow‐Yen‐Desmond
Abstract : In this work, the modulation of the magnetic field locus beneath a microstrip antenna due to placement of feeding probe has been exploited to evolve a simplified single element single layer structure for improved impedance matching and radiation performance. Unlike the earlier investigations, the present study tackles the issue of cross‐polar radiation of microstrip antenna due to its own dominant TM10 mode by achieving the uniformity of field distribution between lower‐ and upper‐half‐sections of a patch to suppress the effective orthogonal radiations (cross‐polar radiations) from the patch corners, without bothering the orthogonal and higher order resonances. Unlike the earlier approaches available in the literature, no slot or short has been made on the patch surface and in the ground plane to suppress cross‐polar radiation, which makes the present structure extremely simple. The proposed bracketed stub‐loaded single layer rectangular microstrip antenna structure exhibits high gain of 8 dBi with 27 dB of co‐cross polar isolation in H plane. The two‐element array constituted with same structure has also been examined and 10 dBi gain with >27 dB of co‐cross polar isolation is obtained. The obtained results are theoretically justified with simulation and measurement.